Country Washer Woman, Trinidad. B.W.I. - (:unkn) unknown (Muir, Marshall and Co. Ltd., Port of Spain, Trinidad, 2008)
Photo of an East Indian girl washing linen by a river. Postcard No. 6455. Includes a Trinidad and Tobago 3 cents stamp.
Colour: Brown and White; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Laundresses--Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; Rivers--Trinidad and Tobago; Trinidad and Tobago; Rural women--Trinidad and Tobago; Country life--Trinidad and Tobago